Atherosclerosis induced by cholesterol and inhibition mechanisms (Revista Española de Fisiología, 1954)
I. A study has been carried aut of the induction of atherosckirosis by the addition of 4 % of cholesterol to the diet of chicks a month c-ld during 12 weeks, when the possible braking action of methionin, magnesio inositol and potassic iodide is observed simultaneously.II. The animals of those groups in which same of the mentioned substances had been added the cholesterol diet were on the wholl less affected in number as well as in intensity, but in all the groups there was one or other animal with atherosclerosic lesions of greater intensity.III. There was an invertet relation between the cyphers of total cholesterolemy and the intensity of the affection the highest cholesteiolemics being observed in the group that were given cholesterol and potassic iodide. The authors suggest the possibility of a physiochemicalstate of cholesterol which prevents its precipitation in the arterial walls